2017
DOI: 10.1016/j.actbio.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Use of hydrogel scaffolds to develop an in vitro 3D culture model of human intestinal epithelium

Abstract: Christine (2017). Use of hydrogel scaffolds to develop an in vitro 3D culture model of human intestinal epithelium. Acta biomaterialia. Copyright and re-use policy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 51 publications
6
39
1
Order By: Relevance
“…This was seen both in Caco-2 monoculture after 3 weeks and in co-cultures where differentiation had taken place. Furthermore, in monoculture and co-culture models no loss of metabolic activity was observed, which may be due to increased flow of nutrients and oxygen by the use of dynamic culture conditions, this effect has been previously seen in Chapter 3 when cells are grown under dynamic culture conditions (Dosh et al 2017). For long-term co-culture experiments, the optimal seeding percentages were 90% Caco-2 / 10% HT29-MTX cells and 75% Caco-2 / 25% HT29-MTX cells.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This was seen both in Caco-2 monoculture after 3 weeks and in co-cultures where differentiation had taken place. Furthermore, in monoculture and co-culture models no loss of metabolic activity was observed, which may be due to increased flow of nutrients and oxygen by the use of dynamic culture conditions, this effect has been previously seen in Chapter 3 when cells are grown under dynamic culture conditions (Dosh et al 2017). For long-term co-culture experiments, the optimal seeding percentages were 90% Caco-2 / 10% HT29-MTX cells and 75% Caco-2 / 25% HT29-MTX cells.…”
Section: Discussionsupporting
confidence: 55%
“…The previous study 139 described in Chapter 3 established 3D in vitro culture models of the intestinal epithelium consisting of monocultures of Caco-2 and HT29-MTX cells layered on L-pNIPAM hydrogel scaffolds under dynamic culture conditions. This model supported the 3D culture of these cells generating villus-like structures and promoted differentiation, mimicking the native intestinal epithelium (Dosh et al 2017). Following gelation 300 µL or 100 µL of 2x10 6 total cells/ml (for each of the 6 cell culture suspensions) in complete media were applied to the surface of hydrogel construct in 48 and 96 well plates respectively, and following a 30 minute cell attachment period a further 200 µL or 150 µL complete media (Caco-2 culture media) was added to each well.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…For example, Kim et al demonstrated that bone morphogenetic protein‐2 (BMP‐2) incorporated thiolated gelatin and poly(ethylene glycol) diacrylate (PEGDA) composite hydrogel scaffold could exhibit effective regeneration of calvarial bone in a rat model 29. Dosh et al utilized poly( N ‐isopropylacrylamide) (PNIPAM) hydrogel as an in vitro 3D culture model for human intestinal cells and suggested that the hydrogel model could be a potential 3D model for intestinal tissue regeneration 30. However, conventional approaches of homogeneous artificial environments have limitations in completely mimicking the natural cellular environment 31…”
Section: Introductionmentioning
confidence: 99%